2016
DOI: 10.1111/mpp.12389
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping‐by‐sequencing‐based genome‐wide association studies on Verticillium wilt resistance in autotetraploid alfalfa (Medicago sativaL.)

Abstract: Verticillium wilt (VW) is a fungal disease that causes severe yield losses in alfalfa. The most effective method to control the disease is through the development and use of resistant varieties. The identification of marker loci linked to VW resistance can facilitate breeding for disease-resistant alfalfa. In the present investigation, we applied an integrated framework of genome-wide association with genotyping-by-sequencing (GBS) to identify VW resistance loci in a panel of elite alfalfa breeding lines. Phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
3
36
1
Order By: Relevance
“…Enhanced resistance to this same pathogen was also obtained through the overexpression of a native isoflavone O-methyltransferase in alfalfa, which likely resulted from increased accumulation of a phytoalexin (medicarpin) in leaves following challenge with the pathogen (He & Dixon, 2000). Similarly, alfalfa plants expressing the M. truncatula ISO-FLAVONE SYNTHASE gene (MtIFS1) also accumulated medicarpin in P. medicaginis-infected leaves; however, the susceptibility of these plants to pathogens has yet to be reported (Deavours & Dixon, 2005 genes in resistance to Verticillium wilt and Aphanomyces euteiches, respectively (Bonhomme et al, 2014;Yu, Zheng, Zhang, Rodringuez, & Main, 2017). This information will almost certainly provide further useful targets for modification in the future.…”
Section: Increasing the Production Of Anti-pathogenic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced resistance to this same pathogen was also obtained through the overexpression of a native isoflavone O-methyltransferase in alfalfa, which likely resulted from increased accumulation of a phytoalexin (medicarpin) in leaves following challenge with the pathogen (He & Dixon, 2000). Similarly, alfalfa plants expressing the M. truncatula ISO-FLAVONE SYNTHASE gene (MtIFS1) also accumulated medicarpin in P. medicaginis-infected leaves; however, the susceptibility of these plants to pathogens has yet to be reported (Deavours & Dixon, 2005 genes in resistance to Verticillium wilt and Aphanomyces euteiches, respectively (Bonhomme et al, 2014;Yu, Zheng, Zhang, Rodringuez, & Main, 2017). This information will almost certainly provide further useful targets for modification in the future.…”
Section: Increasing the Production Of Anti-pathogenic Moleculesmentioning
confidence: 99%
“…For example, transcriptomic analysis of Verticillium wilt‐resistant and susceptible genotypes of the model legume, M. truncatula , indicated that the resistant genotype provided higher basal expression levels of various defense‐related genes, as well as enhanced up‐regulation of genes involved in PAMP‐triggered immunity following infection (Toueni, Ben, Le Ru, Gentzbittel, & Rickauer, ). Similarly, genome‐wide association studies in alfalfa and M. truncatula have implicated various genes in resistance to Verticillium wilt and Aphanomyces euteiches , respectively (Bonhomme et al, ; Yu, Zheng, Zhang, Rodringuez, & Main, ). This information will almost certainly provide further useful targets for modification in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The draw backs of the method are often large amounts of missing data due to low coverage sequencing (Fu and Peterson 2011;Poland et al 2012) and uneven genome coverage, due to the sequence specificity of the chosen restriction enzyme (Beissinger et al 2013). GBS is used for genotyping for a wide range of purposes including for QTL mapping and genomic prediction in many crop and animal species, including for example rice (Spindel et al 2013), tomato (Capel et al 2015;Celik et al 2017;Yu et al 2016), grape (Marrano et al 2017) and livestock species (Gurgul et al 2018). GBS can be successfully adapted to model species like tomato with wellcharacterized reference genomes, as well as to crops without reference genome sequences (Berthouly-Salazar et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of allopolyploid SNP arrays include cotton (Hulse-Kemp et al, 2015), oat (Tinker et al, 2014), oilseed rape (Dalton- Morgan et al, 2014;Clarke et al, 2016), peanut (Pandey et al, 2017), strawberry (Bassil et al, 2015) and wheat (Akhunov et al, 2009;Cavanagh et al, 2013;Wang et al, 2014b;Winfield et al, 2016). Untargeted approaches such as genotyping-by-sequencing have also been applied, for example in autopolyploids such as alfalfa Yu et al, 2017), blueberry (McCallum et al, 2016), bluestem prairie grass (Andropogon gerardii) (McAllister and Miller, 2016), cocksfoot (Dactylis glomerata) (Bushman et al, 2016), potato (Uitdewilligen et al, 2013;Sverrisdóttir et al, 2017), sugarcane (Balsalobre et al, 2017;Yang et al, 2017b) and sweet potato (Shirasawa et al, 2017), and in allopolyploids such as coffee (Moncada et al, 2016), cotton (Islam et al, 2015;Reddy et al, 2017), intermediate wheatgrass (Thinopyrum intermedium) (Kantarski et al, 2017), oat (Chaffin et al, 2016), prairie cordgrass (Spartina pectinata) (Crawford et al, 2016), shepherd's purse (Capsella bursa-pastoris) (Cornille et al, 2016), wheat (Poland et al, 2012;Edae et al, 2015) and zoysiagrass (Zoysia japonica) (McCamy et al, 2018) (noting that the precise classification of some of these species as auto-or allopolyploids has yet to be conclusively determined). Whatever the technology used, it is clear that we are currently witnessing an explosion of interest in polyploid genomics.…”
Section: Genotyping Technologiesmentioning
confidence: 99%